THE INFLUENCE OF PROFESSIONALISM AND WORK STRESS ON THE PERFORMANCE OF WIDYATAMA UNIVERSITY LECTURERS DURING THE COVID-19 PANDEMIC - Melina, Rima; Septiani, Nurul Rizki; Putri, Cania Dwi Fhanadya; Nurjanah, Eka; Gardanea, Alia; Brahmana, Sunardi Sembiring (CENTRAL ASIA AND THE CAUCASUS, 2022)
The Covid-19 pandemic that has not yet recovered, making educational institutions have not been able to fully right activities such as normal conditions. This research aims to examine the effect of professionalism and work stress on performance of lecturers of Widyatama University Bandung during the Covid-19 pandemic. Performance of a lecturer was related to the competence and clarity of his duties. One of the factors that determine a person's work competence is professionalism and work stress. The organization must understand how a person's performance is well formed. One factor that can explain the performance of a worker at the time of the Covid-19 pandemic like this is the clarity of tasks that are systematically measured and relieve work stress from each worker. individual workers. Data for this study was obtained through questionnaires, distributed to lecturers using google form. Seventy questionnaires were returned and completely filled. The results of hypothesis testing showed that professionalism had a positive effect on lecturers’ performance, and work stress had a negative effect on lecturers’ performance. The implication of this research is that the management of educational institutions must be able to develop details of the work and clarity of roles/authorities that are deemed appropriate and attractive. If the perception of lecturers meets their expectation about the details of the work or tasks he does, then their performance will be high. Professionalism and good management of work stress will trigger the formation of higher performance.